Effects of process air conditions and switching cycle period on dehumidification performance of desiccant-coated heat exchangers. (2nd January 2017) - Chang, Chih-Chang; Luo, Win-Jet; Lu, Chi-Wen; Cheng, Yu-Sheng; Tsai, Bo-Yi; Lin, Zhi-Hua
Abstract : This study investigated the dehumidification effect of silica gel and sodium polyacrylate desiccants coated on fin and tube heat exchangers under various humidity and temperature conditions. In the system, the two desiccant-coated heat exchangers are periodically operated in mass equilibrium states between dehumidification and regeneration processes. The corresponding cyclic switching times between the two processes are investigated to determine suitable switching times that will further improve the operational efficiency of the system. The experimental results show that while water at a temperature of 50°C was supplied during the regeneration process, the sorption ability was greater and the vapor was discharged in a shorter period of the regeneration process for the sodium polyacrylate desiccant than for silica gel. Thus, the moisture sorption ability of sodium polyacrylate in the system is superior to that of silica gel under the same operational conditions. Suitable cyclic switching times for both desiccants in different operational conditions were recommended in this study. By adapting the corresponding recommended switching times in the dehumidification and regeneration processes, a 10–14% increase in thermal performance can be attained for the two desiccants under the operating conditions.